A General Equilibrium Analysis of Conjunctive Ground and Surface Water Use with an Application to Morocco - Diao, Xinshen (2012)
Groundwater resources (GW) account for nearly 30% of the world's sustainable water supplies. Yet, this resource, which is fraught with externalities, has largely been left unregulated. The economic literature on GW is predominantly of a partial equilibrium type. We analyze GW regulation in a general equilibrium setting, focusing on the stabilization value of GW under natural (drought) and economic (rural-urban water transfer) shocks. A general equilibrium approach allows evaluating direct and indirect effects of GW regulation on agriculture and nonagriculture sectors and extends the scope for water policy. The analysis is applied to Morocco by extending an existing computable general equilibrium (CGE) model to include ground and surface water (SW) resources. We study effects of (i) an increase in GW extraction cost (e.g., as a result of prolonged extraction beyond natural recharge that lowers the aquifer's water table), (ii) a transfer of SW from rural (irrigation) to urban (domestic) use, and (iii) a reduction of water availability due to severe drought. We estimate the value of GW and assess the direct (partial equilibrium) and indirect (general equilibrium) impacts. We find that GW plays a critical role in mitigating the negative effects of these types of shocks.